UV visbreaking protective film and preparation method thereof

By using a combination of specific resin and photoinitiator in the UV adhesive-reducing protective film, the double curing and debonding of epoxy-double bonds is achieved, solving the problems of more residual glue and poor acid and alkali resistance after the unbonding of the traditional UV adhesive-reducing protective film, and improving the chemical resistance and debonding effect of the protective film.

CN119684923APending Publication Date: 2025-03-25HUIZHOU HONGTIAN ELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411965960.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

After the traditional UV adhesive reduction protection film has a large amount of residual glue after dismantling, and has poor tolerance to strong acids and alkalis, so it cannot effectively protect the metal foil, resulting in side etching, shedding or incomplete lines in the etching process.

Method used

The main resin, polyurethane acrylate oligomer, multifunctional epoxidized alicyclic compounds, multifunctional acrylate monomers, tackifiers and photoinitiators are used as formula raw materials. The epoxy-double bond double curing and debonding are achieved through a solvent-free, photo-driven free radical/cation mixing initiation system.

Benefits of technology

It is realized that there is no obvious residual glue after sticking. The glue layer is resistant to high temperatures, acid and alkali, and has good adhesion to metals. It avoids side corrosion and fall off problems in the etching process. It has a good debonding effect, is easy to transfer, and will not stick to metal lines, which leads to misalignment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218354500000051
    Figure BDA0005218354500000051
  • Figure BDA0005218354500000052
    Figure BDA0005218354500000052
  • Figure BDA0005218354500000061
    Figure BDA0005218354500000061
Patent Text Reader

Abstract

The invention discloses a UV visbreaking protective film and a preparation method thereof. The UV visbreaking protective film comprises the following first raw materials in parts by mass: 150 parts of matrix resin; 1 part to 10 parts of a polyurethane acrylate oligomer; 8 to 30 parts of a multifunctional epoxidized alicyclic compound; 10 to 35 parts of a multifunctional acrylate monomer; 4 to 15 parts of a tackifier; 3 to 10 parts of a photoinitiator; wherein the matrix resin is prepared from an alicyclic epoxy acrylate monomer, acrylic acid-2-ethylhexyl ester, methyl methacrylate, monofunctional polyurethane acrylate, an acrylic acid monomer and azodiisobutyronitrile. The UV visbreaking protective film provided by the invention has the advantages of no adhesive residue in visbreaking and excellent chemical resistance, can be suitable for an etching process, and is not easy to permeate to cause lateral erosion or fall off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical films, and in particular to a UV viscosity-reducing protective film and a preparation method thereof. Background Art

[0002] In the production of flexible printed circuit boards (FPC) / heating sheets, a tack-reducing protective film is required for protection. After the metal foil has completed the circuit etching and transfer processes, the tack-reducing protective film can be peeled off. The tack-reducing protective film is applied to the semi-finished product to provide temporary protection and fixation. After the production process is completed, the tack-reducing protective film can be quickly de-adhesed by UV irradiation / heating, so that the tack-reducing protective film is separated from the protected object.

[0003] At present, UV anti-viscosity protective film is mainly based on polyacrylate adhesives. Conventional polyacrylate adhesives have the problem of a large amount of residual adhesive after UV debonding. After debonding, a small amount of components will remain and affect the subsequent process; and the tolerance to strong acids and alkalis is poor, and it cannot protect the metal foil well. In the etching process, etching liquid penetration is prone to occur, resulting in side corrosion of the metal circuit, shedding or incomplete circuit problems. Summary of the invention

[0004] The invention provides a UV anti-viscosity protective film and a preparation method thereof, so as to solve the technical problems of much adhesive residue after debonding and poor protection ability of the conventional UV anti-viscosity protective film.

[0005] In order to solve the above technical problems, in a first aspect, an embodiment of the present invention provides a UV viscosity-reducing protective film, comprising the following first raw materials by mass fraction:

[0006] Main resin 150 parts;

[0007] 1 to 10 parts of polyurethane acrylate oligomer;

[0008] 8 to 30 parts of a multifunctional epoxidized alicyclic compound;

[0009] 10 to 35 parts of multifunctional acrylate monomer;

[0010] 4 to 15 parts of tackifier;

[0011] 3 to 10 parts of photoinitiator;

[0012] Wherein, the main resin is composed of the following second raw materials in percentage by mass:

[0013] Alicyclic epoxy acrylate monomer 8% to 15%;

[0014] 2-Ethylhexyl acrylate 40% to 70%;

[0015] Methyl methacrylate 15% to 25%;

[0016] Monofunctional polyurethane acrylate 5% to 15%;

[0017] Acrylic monomer 1% to 5%;

[0018] Azobisisobutyronitrile 1%~2%.

[0019] In some embodiments, the main resin is prepared by heating the second raw material at 60°C to 80°C for 4 hours and keeping it at 90°C for 2 hours under a nitrogen atmosphere; the main resin has a solid content of 40%, a Tg value of -30°C to 30°C, and a molecular weight of 10,000 to 5,000,000.

[0020] In some embodiments, the molecular weight of the main resin is 150,000-1,500,000.

[0021] In some embodiments, the alicyclic epoxy acrylate monomer includes any one or more of 7-oxacyclo[4.1.0]hept-3-ylmethyl methacrylate, 1,2-epoxy-4-vinylcyclohexane and 3,4-epoxycyclohexyl methacrylate.

[0022] In some embodiments, the monofunctional polyurethane acrylate includes but is not limited to YC1138S from Jining Tangyi Chemical Co., Ltd.

[0023] In some embodiments, the acrylic acid monomer includes any one or more of acrylic acid, methacrylic acid, maleic acid, itaconic acid, fumaric acid, maleic anhydride and itaconic anhydride.

[0024] In some embodiments, the polyurethane acrylate oligomer comprises 4765, Zhanxin 880, Allnew At least two of 8896, Sartomer CN9006NS, Sartomer CN9010NS and Sartomer CN9021 NS.

[0025] In some embodiments, the multifunctional epoxidized alicyclic compound includes any one or more of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester, bis((3,4-epoxycyclohexyl)methyl)adipate and tetrahydroindene diepoxide.

[0026] In some embodiments, the multifunctional acrylic monomer includes any one or more of trimethylolpropane triacrylate, triethylene glycol diacrylate, pentaerythritol tetraacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, dipentaerythritol hexaacrylate and tricyclodecane dimethanol diacrylate.

[0027] In some of the embodiments, the tackifier includes at least one of a rosin resin, a terpene resin, and a phenolic resin;

[0028] The photoinitiator comprises a free radical photoinitiator and a cationic photoinitiator in a mass ratio of 10:(1-100), and the mass ratio is preferably 10:(2-50), and more preferably 10:(5-25).

[0029] Free radical photoinitiators include, but are not limited to, 184, 1173 and TPO, and cationic photoinitiators include, but are not limited to, diaryliodonium salts, triarylsulfonium salts and iron arene salts.

[0030] In a second aspect, a method for preparing a UV anti-viscosity protective film provided by an embodiment of the present invention comprises the following steps:

[0031] Step 1, weighing the first raw material of the UV viscosity-reducing protective film according to the mass fraction, and mixing the first raw material evenly to obtain an adhesive;

[0032] Step 2: coating the adhesive on the transparent PET-based original film, and then drying it in a four-section gradient oven at 80° C., 120° C., 145° C. and 170° C. at a line speed of 20 m / min to obtain an adhesive film;

[0033] Step 2: Cover the adhesive film of step 2 with a PET release protective film, place it in an oven at 60° C. for 24 hours, and obtain a UV anti-viscosity protective film.

[0034] Compared with the prior art, the present invention has at least the following beneficial effects:

[0035] The present invention uses a main resin, a polyurethane acrylate oligomer, a multifunctional epoxidized alicyclic compound, a multifunctional acrylate monomer, a tackifier and a photoinitiator as the formula raw materials of the UV anti-viscosity protective film, and realizes epoxy-double bond dual curing and debonding through a solvent-free, light-driven free radical / cation mixed initiation system. Before debonding, the adhesive layer is resistant to high temperatures, acids and alkalis, has excellent adhesion to metals, and can avoid problems such as side corrosion and falling off during the etching process. It has a good fixing, bearing and protective effect on the metal foil; after debonding, the debonding effect is good and there is no obvious residual glue. It is easy to transfer and will not adhere to the metal circuit to cause circuit dislocation. Compared with traditional acrylic UV anti-viscosity adhesive films, the UV anti-viscosity protective film of the present invention has no residual glue and excellent chemical resistance when debonded, and can be applied to etching processes. It is not easy to be penetrated and eroded or fall off. DETAILED DESCRIPTION

[0036] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0037] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0038] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.

[0039] In addition, the indefinite articles "a" and "an" before the elements or components of the present invention have no restrictions on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number is obviously intended to be in the singular form.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0041] The raw materials used in the preparation example of the main resin of the embodiment of the present invention are shown in Table 1:

[0042] Table 1

[0043]

[0044] Preparation of main resin:

[0045] 10 parts of 7-oxacyclo[4.1.0]heptane-3-ylmethyl methacrylate, 50 parts of 2-ethylhexyl acrylate, 24 parts of methyl methacrylate, 11 parts of YC1138S, 2 parts of maleic anhydride, 1 part of itaconic acid, 2 parts of AIBN, 81 parts of ethyl acetate and 81 parts of toluene were placed in a reaction kettle, heated at 70°C for 4 hours under a nitrogen atmosphere, and then kept at 90°C for 2 hours to obtain a main resin.

[0046] The raw materials used for the UV viscosity-reducing protective film of the embodiment of the present invention are shown in Table 2:

[0047] Table 2

[0048]

[0049]

[0050] Test method:

[0051] Sample preparation: Cut the prepared UV anti-viscosity film into test strips of 25mm*70mm.

[0052] Initial peeling force test: This test is conducted according to ASTM D3330. The sample is falsely attached to a SUS test mirror steel sheet and rolled twice using an automatic rolling roller (wheel weight 2kg, 300mm / min travel speed). Immediately perform a peeling force test at an angle of 180° and a speed of 300mm / min.

[0053] Chemical resistance test: This test is carried out according to IPC-TM650 2.3.2 method. The test samples are prepared in the same way as the initial peeling force test. The samples are immersed in 2mol / L HCl and taken out after 30 minutes. The peeling force is tested in the same way as the initial peeling force method, and the peeling force reduction rate is calculated.

[0054] Peel force test after debonding: Same as the initial peel force test, after preparing the sample, irradiate the sample with UV light of 120mW / cm2 and 365nm wavelength for 1min, then perform the peel force test and observe the appearance of the peeled surface.

[0055] Example 1

[0056] Components: main resin 150 parts, EBECRYL 8896 2 parts, CN9010 NS 5 parts, Celloxide2021p 15 parts, EM263 10 parts, ETERMER 2204 10 parts, PR12603 10 parts, GR184 2 parts, GR-FMT 4 parts;

[0057] Preparation method: Mix the above components evenly to obtain an adhesive; apply the adhesive on a 100um transparent PET base film, and then dry it in a four-section gradient oven at 80°C, 120°C, 145°C and 170°C at a line speed of 20m / min to obtain an adhesive film; cover it with a PET release protective film, place it in a 60°C oven for aging for 24h, and obtain a UV anti-viscosity protective film.

[0058] Example 2

[0059] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 3 parts of CN9010 NS, 20 parts of Celloxide2021p, 10 parts of EM263, 10 parts of ETERMER 2204, 12 parts of PR12603, 3 parts of GR184, and 4 parts of GR-FMT; the preparation method is the same as that in Example 1.

[0060] Example 3

[0061] Components: 150 parts of main resin, 1 part of EBECRYL 8896, 6 parts of CN9010 NS, 25 parts of Celloxide2021p, 12 parts of EM263, 10 parts of ETERMER 2204, 12 parts of PR12603, 2 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0062] Example 4

[0063] Components: 150 parts of main resin, 8 parts of EBECRYL 8896, 0 parts of CN9010 NS, 35 parts of Celloxide2021p, 12 parts of EM263, 8 parts of ETERMER 2204, 14 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that in Example 1.

[0064] Comparative Example 1

[0065] Components: 150 parts of main resin, 4 parts of EBECRYL 8896, 3 parts of CN9010 NS, 100 parts of Celloxide2021p, 12 parts of EM263, 10 parts of ETERMER 2204, 10 parts of PR12603, 2 parts of GR184, and 4 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0066] Comparative Example 2

[0067] Components: 150 parts of main resin, 2 parts of EBECRYL 8896, 3 parts of CN9010 NS, 0 parts of Celloxide2021p, 12 parts of EM263, 10 parts of ETERMER 2204, 10 parts of PR12603, 2 parts of GR184, and 4 parts of GR-FMT; the preparation method is the same as that in Example 1.

[0068] Table 3 Performance test results of Examples 1 to 4 and Comparative Examples 1 to 2

[0069]

[0070]

[0071] Comparative Example 1 is compared with Examples 1 to 4. Excessive epoxidized alicyclic compounds are added in Comparative Example 1, resulting in a serious decrease in the cohesive energy of the adhesive layer and a significant decrease in chemical resistance. After UV irradiation, the adhesive strength of the adhesive layer deteriorates. Although the debonding peeling force is very low, there is a large amount of residual adhesive on the metal surface. Comparative Example 2 is compared with Examples 1 to 4. No epoxidized alicyclic compounds are added, resulting in a certain decrease in the initial peeling force of the adhesive layer and a significant decrease in chemical resistance. After UV irradiation, the debonding peeling force is too large and cannot meet production requirements.

[0072] Example 5

[0073] Components: 150 parts of main resin, 4 parts of EBECRYL 8896, 4 parts of CN9010 NS, 18 parts of Celloxide2021p, 12 parts of EM263, 18 parts of ETERMER 2204, 14 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0074] Example 6

[0075] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 3 parts of CN9010 NS, 20 parts of Celloxide2021p, 25 parts of EM263, 0 parts of ETERMER 2204, 14 parts of PR12603, 4 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0076] Example 7

[0077] Components: 150 parts of main resin, 1 part of EBECRYL 8896, 8 parts of CN9010 NS, 22 parts of Celloxide2021p, 0 parts of EM263, 25 parts of ETERMER 2204, 10 parts of PR12603, 4 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0078] Comparative Example 3

[0079] Components: 150 parts of main resin, 6 parts of EBECRYL 8896, 6 parts of CN9010 NS, 20 parts of Celloxide2021p, 0 parts of EM263, 0 parts of ETERMER 2204, 10 parts of PR12603, 2 parts of GR184, and 4 parts of GR-FMT; the preparation method is the same as that in Example 1.

[0080] Comparative Example 4

[0081] Components: 150 parts of main resin, 2 parts of EBECRYL 8896, 3 parts of CN9010 NS, 22 parts of Celloxide2021p, 55 parts of EM263, 0 parts of ETERMER 2204, 10 parts of PR12603, 4 parts of GR184, and 8 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0082] Comparative Example 5

[0083] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 3 parts of CN9010 NS, 22 parts of Celloxide2021p, 0 parts of EM263, 60 parts of ETERMER 2204, 10 parts of PR12603, 4 parts of GR184, and 8 parts of GR-FMT; the preparation method is the same as that in Example 1.

[0084] Comparative Example 6

[0085] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 3 parts of CN9010 NS, 22 parts of Celloxide2021p, 50 parts of EM263, 50 parts of ETERMER 2204, 10 parts of PR12603, 4 parts of GR184, and 8 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0086] Table 4 Performance test results of Examples 5 to 7 and Comparative Examples 3 to 6

[0087]

[0088] Comparative Example 3 is compared with Examples 5 to 7. Without adding multifunctional acrylate monomer, the debonding speed is slow. After UV irradiation, the debonding peeling force is too large and there is a large amount of residual adhesive. Comparative Example 4 is compared with Examples 5 to 7. Only excessive EM263 is used, which leads to a very low initial peeling force. Comparative Example 5 is compared with Examples 5 to 7. Only excessive ETERMER 2204 is used, which leads to a very low initial peeling force and poor debonding peeling force after UV irradiation. Comparative Example 6 is compared with Examples 5 to 7. Excessive EM263 and excessive ETERMER 2204 are used, which leads to too low initial peeling force.

[0089] Example 8

[0090] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 5 parts of CN9010 NS, 22 parts of Celloxide2021p, 12 parts of EM263, 17 parts of ETERMER 2204, 14 parts of PR12603, 4 parts of GR184, and 2 parts of GR-FMT; the preparation method is the same as that in Example 1.

[0091] Example 9

[0092] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 5 parts of CN9010 NS, 22 parts of Celloxide2021p, 12 parts of EM263, 17 parts of ETERMER 2204, 14 parts of PR12603, 2 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0093] Comparative Example 7

[0094] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 5 parts of CN9010 NS, 18 parts of Celloxide2021p, 12 parts of EM263, 17 parts of ETERMER 2204, 14 parts of PR12603, 4 parts of GR184, and 0 parts of GR-FMT; the preparation method is the same as that in Example 1.

[0095] Comparative Example 8

[0096] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 5 parts of CN9010 NS, 17 parts of Celloxide2021p, 15 parts of EM263, 17 parts of ETERMER 2204, 14 parts of PR12603, 0 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0097] Comparative Example 9

[0098] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 5 parts of CN9010 NS, 17 parts of Celloxide2021p, 12 parts of EM263, 17 parts of ETERMER 2204, 14 parts of PR12603, 7 parts of GR184, and 7 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0099] Table 5 Performance test results of Examples 8 to 9 and Comparative Examples 7 to 9

[0100]

[0101]

[0102] Comparative Example 7 is compared with Examples 8 and 9. No cationic photoinitiator is added, and the epoxy groups are not fully cross-linked, resulting in failure in debonding. Comparative Example 8 is compared with Examples 8 and 9. No free radical photoinitiator is added, and the debonding peeling force is too large, and there is residual glue. Comparative Example 9 is compared with Examples 8 and 9. Excessive free radical initiator / cationic initiator is added. The excessive initiator will have a small amount of residue and will corrode the metal surface to form irregular oxidation lines.

[0103] Example 10

[0104] Components: 150 parts of main resin, 5 parts of EBECRYL 8896, 5 parts of CN9010 NS, 20 parts of Celloxide2021p, 10 parts of EM263, 16 parts of ETERMER 2204, 12 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0105] Embodiment 11

[0106] Components: 150 parts of main resin, 8 parts of EBECRYL 8896, 1 ​​part of CN9010 NS, 20 parts of Celloxide2021p, 10 parts of EM263, 17 parts of ETERMER 2204, 12 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0107] Example 12

[0108] Components: 150 parts of main resin, 2 parts of EBECRYL 8896, 1 ​​part of CN9010 NS, 20 parts of Celloxide2021p, 10 parts of EM263, 15 parts of ETERMER 2204, 12 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0109] Comparative Example 10

[0110] Components: 150 parts of main resin, 0 parts of EBECRYL 8896, 0 parts of CN9010 NS, 25 parts of Celloxide2021p, 10 parts of EM263, 15 parts of ETERMER 2204, 15 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0111] Comparative Example 11

[0112] Components: 150 parts of main resin, 20 parts of EBECRYL 8896, 20 parts of CN9010 NS, 25 parts of Celloxide2021p, 10 parts of EM263, 15 parts of ETERMER 2204, 15 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0113] Table 6 Performance test results of Examples 10 to 12 and Comparative Examples 10 to 11

[0114] Initial peeling force kgf / 25mm Peel force after viscosity reduction gf / 25mm Viscosity reduction effect Example 10 2.2 9.1 No residual glue Embodiment 11 2.0 7.7 No residual glue Example 12 1.6 8.1 No residual glue Comparative Example 10 0.8 13.7 No residual glue Comparative Example 11 0.6 15.9 There is residual glue

[0115] Comparison of Example 10 with Examples 10-12 shows that no polyurethane acrylate oligomer is added, and the adhesive layer has poor metal wetting and low peeling force. Comparison of Example 11 with Examples 10-12 shows that excessive polyurethane acrylate oligomer is added, which will lead to poor adhesion after debonding, and the adhesive layer will be transferred to the metal surface over a large area.

[0116] Embodiment 13

[0117] Components: 150 parts of main resin, 4 parts of EBECRYL 8896, 5 parts of CN9010 NS, 22 parts of Celloxide2021p, 12 parts of EM263, 12 parts of ETERMER 2204, 15 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that in Example 1.

[0118] Comparative Example 12

[0119] Components: 150 parts of EBECRYL 3500 (40%), 4 parts of EBECRYL 8896, 5 parts of CN9010 NS, 22 parts of Celloxide 2021p, 12 parts of EM263, 12 parts of ETERMER 2204, 15 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0120] Comparative Example 13

[0121] Components: CN111LV NS (40%) 150 parts, EBECRYL 8896 4 parts, CN9010 NS 5 parts, Celloxide2021p 22 parts, EM263 12 parts, ETERMER 2204 12 parts, PR12603 15 parts, GR184 3 parts, GR-FMT 5 parts; preparation method is the same as Example 1.

[0122] Comparative Example 14

[0123] Components: 150 parts of Therban XT VP (40%), 4 parts of EBECRYL 8896, 5 parts of CN9010 NS, 22 parts of Celloxide 2021p, 12 parts of EM263, 12 parts of ETERMER 2204, 15 parts of PR12603, 3 parts of GR184, and 5 parts of GR-FMT; the preparation method is the same as that of Example 1.

[0124] Comparative Example 15

[0125] Components: Therban XT VP (40%) 75 parts, EBECRYL 3500 (40%) 75 parts, EBECRYL 8896 4 parts, CN9010 NS 5 parts, Celloxide 2021p 22 parts, EM263 12 parts, ETERMER 220412 parts, PR12603 15 parts, GR184 3 parts, GR-FMT 5 parts; preparation method is the same as Example 1.

[0126] Table 7 Performance test results of Example 13 and Comparative Examples 12 to 15

[0127]

[0128] Comparative Example 12 is compared with Example 13. Glycidyl ester / ether-modified epoxy polyacrylate is used to replace the main resin. The initial bonding is poor / the initial peeling force is low, and the curing is too slow. It takes 2 hours before most of the crosslinking is completed to complete the debonding. Comparative Example 13 is compared with Example 13. Epoxy acrylate oligomer is used to replace the main resin. Because the molecular weight is too low, the UV viscosity-reducing adhesive cannot form a film. Comparative Example 14 is compared with Example 13. The main resin is replaced by carboxylated hydrogenated nitrile rubber with a large molecular weight. The initial peeling force is low, and the debonding effect is not good. The peeling force after debonding is too large. Comparative Example 15 is compared with Example 13. Epoxy polyacrylate is used to replace the main resin together with carboxylated hydrogenated nitrile rubber. The peeling force is improved, but the debonding effect is poor.

[0129] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0130] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A UV anti-viscosity protective film, characterized in that: The invention comprises the following first raw materials by mass fraction: Main resin 150 parts; 1 to 10 parts of polyurethane acrylate oligomer; 8 to 30 parts of a multifunctional epoxidized alicyclic compound; 10 to 35 parts of multifunctional acrylate monomer; 4 to 15 parts of tackifier; 3 to 10 parts of photoinitiator; Wherein, the main resin is composed of the following second raw materials in percentage by mass: Alicyclic epoxy acrylate monomer 8% to 15%; 2-Ethylhexyl acrylate 40% to 70%; Methyl methacrylate 15% to 25%; Monofunctional polyurethane acrylate 5% to 15%; Acrylic monomer 1% to 5%; Azobisisobutyronitrile 1%~2%.

2. The UV anti-viscosity protective film according to claim 1, characterized in that: The main resin is prepared by heating the second raw material at 60°C to 80°C for 4 hours and keeping it at 90°C for 2 hours under a nitrogen atmosphere; the main resin has a solid content of 40%, a Tg value of -30°C to 30°C, and a molecular weight of 10,000 to 5,000,000.

3. The UV anti-viscosity protective film according to claim 1, characterized in that: The molecular weight of the main resin is 150,000 to 1,500,000.

4. The UV anti-viscosity protective film according to claim 1, characterized in that: The alicyclic epoxy acrylate monomer includes any one or more of 7-oxacyclo[4.1.0]heptane-3-ylmethyl methacrylate, 1,2-epoxy-4-vinylcyclohexane and 3,4-epoxycyclohexyl methacrylate.

5. The UV viscosity-reducing protective film according to claim 1, characterized in that: The acrylic acid monomer includes any one or more of acrylic acid, methacrylic acid, maleic acid, itaconic acid, fumaric acid, maleic anhydride and itaconic anhydride.

6. The UV anti-viscosity protective film according to claim 1, characterized in that: The polyurethane acrylate oligomer includes allnex 4765, Zhanxin 880, Allnew At least two of 8896, Sartomer CN9006NS, Sartomer CN9010 NS and Sartomer CN9021 NS.

7. The UV viscosity-reducing protective film according to claim 1, characterized in that: The multifunctional epoxidized alicyclic compound includes any one or more of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester, bis((3,4-epoxycyclohexyl)methyl)adipate and tetrahydroindene diepoxide.

8. The UV viscosity-reducing protective film according to claim 1, characterized in that: The multifunctional acrylic monomer includes any one or more of trimethylolpropane triacrylate, triethylene glycol diacrylate, pentaerythritol tetraacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, dipentaerythritol hexaacrylate and tricyclodecane dimethanol diacrylate.

9. The UV anti-viscosity protective film according to claim 1, characterized in that: The tackifier comprises at least one of rosin resin, terpene resin and phenolic resin; The photoinitiator comprises a free radical photoinitiator and a cationic photoinitiator in a mass ratio of 10:(1-100).

10. A method for preparing a UV viscosity-reducing protective film according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1, weighing the first raw material of the UV viscosity-reducing protective film according to the mass fraction, and mixing the first raw material evenly to obtain an adhesive; Step 2: coating the adhesive on the transparent PET-based original film, and then drying it in a four-section gradient oven at 80° C., 120° C., 145° C. and 170° C. at a line speed of 20 m / min to obtain an adhesive film; Step 2: Cover the adhesive film of step 2 with a PET release protective film, place it in an oven at 60° C. for 24 hours, and obtain a UV anti-viscosity protective film.